The Male Mud Crab (Scylla serrata) Moulting Period Using Ablation Methods in Soft Shell Crab Cultivation - B Hutabarat, Geral; Rusliadi, Rusliadi; Mulyadi, Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTIn the cultivation of soft shell crab (Scylla serrata), the duration of moulting is absolutely necessery. Moulting stimulation method of mud crab is the one way to increase soft shell crabproduction. This aims of the study was to determine the effect of eye ablation on the moulting duration of male mud crab. This study uses experimental method and Completely Randomized Design (CRD), which is 4 treatmen levels and 3 repetitions. This study uses 48 male mud crabs. Moulting stimulation methods in this study are right eye ablation, left eye ablation, right and left eye ablation and without ablation (control). Observed parameter includes length of sampling, specific growth rate, survival rate and water quality. The results showed that right eye ablation was the best treatment in accelerating the duration of moulting of 20 days, specific growth rate of 1.74%, and survival rate of 83.33%. Based on the results of the study concluded that the right eye ablation method is good to be applied in stimulating mud crab moulting in increasing the production of soft shell crab.  Keywords : moulting; ablation; moulting period; Growth; Survival Rate;Scylla serrata; Mud Crab